Pola Spasial Kampung Jagalan Ledoksari terhadap Dinamika Lingkungan di Bantaran Sungai Code - Sukma Nuriana Putri; Paulus Bawole; Wiyatiningsih Wiyatiningsih (Institut Nalanda, 2026)
Kampung Jagalan Ledoksari is part of a historic settlement that developed during the reign of Pakualam VII in the early 20th century. This settlement grew along the banks of the Code River through a socio-cultural system passed down from generation to generation, forming a strong relationship between residential space and environmental conditions. Along with urban development, this area faces pressures from urbanization, limited land availability, and recurring disaster risks such as flooding and cold lava flows, which drive environmental dynamics. This study aims to identify changes in the spatial patterns of the Code Riverbank settlement as a response to urban pressures. The focus of the study includes changes in spatial layout, building orientation, and settlement circulation patterns. The research employs a qualitative approach with an ethnographic design, utilizing field observations and in-depth historical spatial mapping to understand the process of spatial adaptation. The findings indicate that changes in the spatial patterns of Kampung Jagalan Ledoksari represent a continuous adaptation process to historical pressures, urbanization, and environmental dynamics. These adaptations gradually and multilayeredly shape transformations in spatial arrangement, building mass, and settlement connectivity. The novelty of this research lies in identifying spatial adaptation strategies that contribute to strengthening the resilience of riverbank settlements against disaster risks and spatial limitations.